Pengelolaan Dana Zakat dalam Pemberdayaan Anak Yatim Program Sanggar Genius Tinjauan Fiqh Zakat: Yayasan Yatim Mandiri Cabang Sragen - Y. Suyoto Arief; Melati Sukma (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Zakat is an Islamic financial instrument that plays a role in improving social welfare, especially in empowering vulnerable groups such as orphans. This research aims to analyze the zakat fund management system in the Sanggar Genius program by the Yatim Mandiri Foundation Sragen Branch and review its suitability with zakat fiqh. The research method used is qualitative research with a case study approach. Data was collected through in-depth interviews, participant observation, and analysis of related documents. The research results show that the management of zakat funds in this program involves systematic stages of planning, collection, distribution and supervision to ensure effectiveness in empowering orphans. The Sanggar Genius program focuses on increasing the literacy, skills and economic independence of orphans through informal education and mentoring. From the perspective of zakat fiqh, the distribution of zakat funds in this program is categorized as part of the asnaf of the poor and needy, not solely based on orphan status. However, this research also found major challenges in implementation, such as the low participation of parents of orphans and a lack of public understanding regarding the principles of productive zakat distribution. In conclusion, optimal management of zakat funds can be a strategic solution in empowering orphans. Therefore, it is necessary to increase zakat literacy in society and collaborate with various parties to increase the effectiveness of zakat-based programs in supporting sustainable social development.